THE CONTENT OF COMMUNICATION FUNCTIONS IN THE SOCIALIZATION OF STUDENTS - Nodira HAKBERDIEVA (Scholar Express Journal, 2024)
This article is written about the essence of communication functions in the socialization of students, communication functions in the process of socialization of students as a pedagogical problem, and the current state of communication functions in the process of socialization of students
Keywords: student; socialization; communication; function